Kary sekwencyjne orzeczone na podstawie art. 37b k.k. — wybrane problemy związane z ich wykonaniem - Raglewska, Joanna (Wydawnictwo Uniwersytetu Wrocławskiego, 2019)
The article concerns problems with the execution of the sequence of two punish-ments: imprisonment and restriction of liberty, imposed on the basis of Art. 37b of the Penal Code. This paper begins with a review of the literature on terminology or the term: “mixed penalty.” We cannot discuss this problem without considering also concrete ex-amples of aims and functions of the new institution. The author presents considerations regarding modifications of carrying out penalties, e.g. application of conditional release, serving a sentence in electronic supervision in the context of the author’s own research.
Keywords: kara; kolejność kar; kara mieszana; kara pozbawienia wolności; ograniczenie wolności; warunkowe zwolnienie